2021
DOI: 10.1016/j.breast.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening using synthesized two-dimensional mammography: A systematic review and meta-analysis

Abstract: We conducted a systematic review and meta-analysis to compare the screening performance of synthesized mammography (SM) plus digital breast tomosynthesis (DBT) with digital mammography (DM) plus DBT or DM alone. Methods: Medline, Embase, Web of Science, and the Cochrane Library databases were searched from January 2010 to January 2021. Eligible population-based studies on breast cancer screening comparing SM/DBT with DM/DBT or DM in asymptomatic women were included. A random-effect model was used in this meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
(61 reference statements)
1
7
0
1
Order By: Relevance
“…There was excellent agreement between the readers in BI-RADS category. We found high level of agreement between the SM+DBT and FFDM+DBT in each of the readers which is consistent with the results of systematic review conducted by Baoqi zeng et al suggesting SM+DBT could replace FFDM+DBT for breast cancer screening [15] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There was excellent agreement between the readers in BI-RADS category. We found high level of agreement between the SM+DBT and FFDM+DBT in each of the readers which is consistent with the results of systematic review conducted by Baoqi zeng et al suggesting SM+DBT could replace FFDM+DBT for breast cancer screening [15] .…”
Section: Discussionsupporting
confidence: 90%
“…David Gur et al, found that SM+DBT had comparable specificity, but slightly lower sensitivity compared with FFDM+DBT [20] , [21] . Conducted numerous clinical studies afterwards suggested comparable results between using SM+DBT and FFDM+DBT [10] , [11] , [12] , [13] , [14] , [15] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the use of DM + DBT implies a twofold increase in the radiation dose, which is not acceptable for the screening of asymptomatic women. Synthesized mammograms (SM) consist of twodimensional images that are generated from the DBT data to prevent exposure to additional radiation doses; SM + DBT have been used to replace DM + DBT for the screening process [1][2][3]. However, DBT is commonly used in combination with DM or SM.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SM maintains the benefits of DBT by accentuating the data volume on the single two-dimensional SM data. Three systemic reviews show that SM + DBT can replace DM + DBT in screening [1,4,5]. Also, several studies have successfully shown that SM alone as non-inferior to DM alone in a diagnostic setting [6][7][8].…”
Section: Introductionmentioning
confidence: 99%